Acupuncture Regulates the Unfolded Protein Response and Inhibits Apoptosis in a Rat Model of Heroin Relapse. Issue 6 (December 2016) - Zhang, Yang; Cai, Xing-Hui; Zhang, Rong-Jun; Hou, Xiao-Rong; Song, Xiao-Ge; Wu, Sheng-Bing; Yu, Shuang; Cao, Jiang-Peng
Object: To explore the unfolded protein response (UPR) in the hippocampus of rats undergoing heroin relapse and the mechanisms underlying the acupuncture-mediated inhibition of brain damage caused by heroin relapse. Methods: 60 Sprague-Dawley rats (30 females and 30 males) were randomly divided into four groups: Control group, Heroin group, Heroin+acupuncture group, and Heroin+methadone group (n=15 each). In the latter three groups, a model of heroin addiction was established by successive increments of intramuscular heroin injections for 8 days, according to the exposure (addiction)→detoxification method. A UPR RT 2 Profiler PCR array was used to screen for differentially expressed genes in the hippocampus. Apoptosis was detected by terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) staining. The protein expression levels of the following three differentially expressed genes were detected by Western blot to validate the results of the PCR array: heat shock protein (HSP)70, HSP105, and valosin-containing protein (Vcp). Results: The UPR RT 2 Profiler PCR Array detection results indicated that acupuncture increased the expression levels of the molecular chaperones HSP70, HSP105, and Vcp. The degree of neuronal apoptosis in the hippocampus of rats in the Heroin+acupuncture and Heroin+methadone groups was significantly reduced compared with the untreated Heroin group (p<0.01). Protein expression of HSP70, HSP105, and Vcp in the Heroin+acupuncture and Heroin+methadone groups was significantly higher than the Heroin group (p<0.01). Conclusions: The positive effects of acupuncture on brain damage caused by heroin may be closely related to up-regulation of HSP70, HSP105, and Vcp, and reduced apoptosis.